2007
DOI: 10.1021/la7007683
|View full text |Cite
|
Sign up to set email alerts
|

Micro- and Nanopatterned Star Poly(ethylene glycol) (PEG) Materials Prepared by UV-Based Imprint Lithography

Abstract: A UV-based imprint lithography method is used for the direct surface structuring of hydrogel-based biomaterials, which are prepared from a family of tailor-made star poly(ethylene glycol) formulations. Bulk star poly(ethylene glycol) (PEG) hydrogels are fabricated by cross-linking acrylate-functionalized star PEG macromolecules. Cross-linking is achieved by radical reactions initiated by UV irradiation. This UV-curable star PEG formulation allows templating of mold structures to yield a stable, stand-alone, el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 47 publications
1
47
0
Order By: Relevance
“…UV-initiated crosslinking of PEO with pentaerythritol triacrylate (PETA) or other radical crosslinkers [8] is becoming increasingly popular since PEO can be crosslinked in both solution and solid state [9,10]. The inclusion of PETA to form crosslinked PEO has been used in biomedical applications such as hydrogels [11,12] and micelles [13] for drug delivery, or to form chemically patterned surfaces for cell studies [14]. However, to our knowledge, the effect of PETA crosslinker on the biocompatibility of PEO-based materials has not been systematically investigated.…”
Section: Introductionmentioning
confidence: 99%
“…UV-initiated crosslinking of PEO with pentaerythritol triacrylate (PETA) or other radical crosslinkers [8] is becoming increasingly popular since PEO can be crosslinked in both solution and solid state [9,10]. The inclusion of PETA to form crosslinked PEO has been used in biomedical applications such as hydrogels [11,12] and micelles [13] for drug delivery, or to form chemically patterned surfaces for cell studies [14]. However, to our knowledge, the effect of PETA crosslinker on the biocompatibility of PEO-based materials has not been systematically investigated.…”
Section: Introductionmentioning
confidence: 99%
“…The crosslinking reaction was initiated by a UV-based radical reaction with benzoin methyl ether as photoinitiator (PI) and an additional crosslinker (CL) (pentaerythritol triacrylate). Further experimental details concerning the synthesis and the curing conditions can be found in our recent publications (Lensen et al, 2007;Diez et al, 2009). The hydrogel substrates were applied as free-standing bulk gels for 2D cell culture studies.…”
Section: Peg-based Hydrogels Formed By Uv-curing: Patternable Biomatementioning
confidence: 99%
“…The hydrogel substrates were applied as free-standing bulk gels for 2D cell culture studies. Due to the fact that the prepolymer Acr-sP(EO-stat-PO) is liquid before crosslinking, the precursor mixture can be molded in any shape, which has enabled us to imprint desired micro-and nanometer topographic patterns into the hydrogel surface (Lensen et al, 2007;Diez et al, 2009). In the following, the properties of this hydrogel system in view of its use in biomedical applications will be evaluated, e.g.…”
Section: Peg-based Hydrogels Formed By Uv-curing: Patternable Biomatementioning
confidence: 99%
“…Garcia also demonstrated that generation of multivalent extracellular matrix enable controlled introduction of branching, activation of side chain substitution and specific functionalization. 12 Polyglycerol is a water soluble polymer and can be substituted by a variety of functional side groups. The prepolymers can further be linked to biologically active compounds.…”
Section: Bioactivation Of Implant Surfacesmentioning
confidence: 99%